Studying Habits in Higher Education Before and After the Outbreak of the COVID-19 Pandemic - Eva Jereb; Janja Jerebic; Marko Urh (Athens Institute for Education and Research, 2023)
The COVID-19 pandemic has caused many changes in all areas, including education. In this paper, we discuss the changes in the studying habits of higher education students brought about by the new modes of education. The research was conducted in Slovenia at the University of Maribor on a sample of 272 students. We investigated whether there had been changes in studying time, studying space, mode of studying and learning during lectures, social elements, and the advantages and barriers of distance learning. We found differences in certain studying habits related to the time and space of studying which are mainly associated with the prohibition of movement and socializing outside the household. We noticed a decline in motivation and its connection with lowering learning goals and students finding it harder to focus on learning. However, we also found that the new mode of studying brings greater flexibility for students, so some want to continue to study in this way.